2012
DOI: 10.1037/a0027350
|View full text |Cite
|
Sign up to set email alerts
|

Coworker incivility and incivility targets' work effort and counterproductive work behaviors: The moderating role of supervisor social support.

Abstract: This study addresses the relationships between coworker incivility and both work effort and counterproductive work behaviors (CWBs). It was expected that employees who experienced high levels of incivility from their coworkers would report reductions in work effort and higher levels of CWBs. Also, based on the emotion-centered model of work behaviors (Spector & Fox, 2002), it was expected that negative emotions would mediate the relationships between coworker incivility and both work effort and CWBs. Finally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
261
3
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(274 citation statements)
references
References 132 publications
(148 reference statements)
8
261
3
2
Order By: Relevance
“…Second, in a literature dominated by studies on target outcomes (e.g., Penney & Spector, 2005;Sakurai & Jex, 2012), our studies highlight the potential costs of incivility for instigators.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 86%
“…Second, in a literature dominated by studies on target outcomes (e.g., Penney & Spector, 2005;Sakurai & Jex, 2012), our studies highlight the potential costs of incivility for instigators.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 86%
“…Accordingly, in order to observe the negative impact of workplace ostracism on organizational identification and then citizenship behavior, we conducted our first study with a six-month time lag, which has been applied to examine the consequence of workplace ostracism (e.g., Liu, Kwan, Lee, & Hui, 2013) or workplace mistreatment (e.g., Lian, Ferris, Morrison, & Brown, 2014;Tepper, 2000). Because "no one time lag by itself can give a complete understanding of a variable's effects" (Gollob & Reichardt, 1987, p. 82), and several studies have found that workplace ostracism and workplace mistreatment can predict psychological consequences with a two-to three-month lag (e.g., Leung et al, 2011;Sakurai & Jex, 2012), we used a different time frame in Study 2 (10 weeks) to explore the role of time in shaping the identification mechanism.…”
Section: The Present Studiesmentioning
confidence: 99%
“…Despite using SET to explain CWB, Sakurai and Jex's (2012) study is limited to civil servants (nonpolice staff). Within the scope of police officers, Mc Carthy, Trougakos, and Cheng (2016) used SET to explain the performance of police personnel.…”
Section: The Role Of Qwl As a Predictor Of Cwb Based On Social Exchanmentioning
confidence: 99%
“…A sense of responsibility held by all parties arise from the provision of support/ material resources or affective support/trust flowing from the first party to the second party (and vise versa). Sakurai and Jex (2012) used SET to explain CWB. In their study, they explain that the lower the support from superiors (in terms of attention, empathy, appreciation, and information), the higher the employees' tendency to show CWB.…”
Section: The Role Of Qwl As a Predictor Of Cwb Based On Social Exchanmentioning
confidence: 99%
See 1 more Smart Citation